2017
DOI: 10.1177/0898264317747078
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Cognitive Impairment and Likelihood of Frequent Hospital Admissions

Abstract: People with CI are at more risk of frequent HA and the severity of impairment can increase this risk subsequently. Screening for CI at admission can open up the possibility of interventions, hence reducing complications during and after hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…26 Nevertheless, the finding is slightly different from our previous cross-sectional study, which indicated that cognitive impairment could independently increase the risk of HAs among older adults. 9 One of the differences between the previous report and the current study, besides using the longitudinal data, is that the current study focused on people living in the community. Nevertheless, the interactions between cognitive impairment and health problems vary in EF and memory.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…26 Nevertheless, the finding is slightly different from our previous cross-sectional study, which indicated that cognitive impairment could independently increase the risk of HAs among older adults. 9 One of the differences between the previous report and the current study, besides using the longitudinal data, is that the current study focused on people living in the community. Nevertheless, the interactions between cognitive impairment and health problems vary in EF and memory.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, participants diagnosed with dementia were excluded from the regression models. Considering that rehospitalization is more common among older adults with cognitive impairment who live in the community, 9 this study included only community-dwelling older adults in all eight waves (n = 9800, 1225 per wave).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cut‐off for the 10‐word list was six or above being considered as normal and less than three as impaired . Using the combination of the immediate 10‐word recall test and the CDT, cognitive function was categorized into five levels: normal, mild, mild‐to‐moderate, moderate and severe cognitive function …”
Section: Methodsmentioning
confidence: 99%
“…Of those with MCI, 10-15% progress to dementia at a rate of 7.1% per year[ 3 , 4 ]. This increasing trend of MCI cases will increase both direct medical costs, such as hospitalization, physician visits, and long-term care[ 5 ], and indirect costs, such as caregiver support[ 6 ]. Considering the growing number of people with MCI, especially those remaining undiagnosed for a long time, it is critical to identify these cases in the early stages to prevent the progression of diseases and possible consequences, such as falling and repeated hospital admission[ 5 ].…”
Section: Introductionmentioning
confidence: 99%